An Overview of Emotional Exhaustion In Single Working Mothers - Yustisio, Farhan; Setiawati, Farida Agus; Dirham, Izza Fadhlinah (International Journal Labs, 2024)
The problem in this study is that single mothers become workers and carry out multiple roles. This study aims to determine the background of emotional exhaustion in single mothers. The subjects in this study were mothers who were still actively working who had been divorced from their husbands and had at least one child. This research method is descriptive in the form of phenomenology. Data collection methods used are observation and interviews. Data analysis techniques used are data reduction, data presentation and conclusions. The conclusions in this study are (1) single mothers experience physical exhaustion due to carrying out dual roles both as workers in the office and as parents to their children, (2) single mothers have problems controlling emotions, especially related to the upbringing of their children, and (3) single mothers try to overcome their sadness to maintain their mental awareness in carrying out their role as parents for their children.